Program Puasa Sunnah Senin Kamis dalam Penerapan Projek Profil Pelajar Pancasila di SMP Perguruan Islam Ar-Risalah - Yanti, Hidayah; Sitepu, Rizki Ramadhan; Lessy , Zulkifli (Universitas Islam Lamongan, 2025)
The implementation of the Monday Thursday voluntary fasting program as part of the Pancasila Student Profile Project at SMP Perguruan Islam Ar-Risalah is based on the fact that the students, ranging from grades VII to IX (Phase D), are aged between 13 and 15 years. This study employs a qualitative field research method, which systematically collects data directly from the field. The findings of this study show that, first, the impact of the Monday Thursday voluntary fasting program is the development of faith, piety to God Almighty, and noble character, which serve as a bridge for students to strengthen their spiritual attitudes. This is reflected in their commitment to obey Allah’s commands, enthusiasm for studying and understanding religious values, increased patience, and the application of commendable behavior in daily life. Second, the regular and independent practice of the Monday Thursday fasting program helps students develop a sense of personal responsibility, self-control, discipline, and physical health.